2019
DOI: 10.18632/oncotarget.27056
|View full text |Cite
|
Sign up to set email alerts
|

Paucimannosidic glycoepitopes inhibit tumorigenic processes in glioblastoma multiforme

Abstract: Glioblastoma multiforme is an aggressive cancer type with poor patient outcomes. Interestingly, we reported previously a novel association between the little studied paucimannosidic N -linked glycoepitope and glioblastoma. Paucimannose has only recently been detected in vertebrates where it exhibits a very restricted tumor-specific expression. Herein, we demonstrate for the first time a very high protein paucimannosylation in human grade IV glioblastoma and U-87MG and U-138MG glioblastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…Similar cancer cell surface expression of PMGs was detected for a related human glioblastoma cell line (U138MG) (data not shown). Immunofluorescence experiments conducted with these and other human cancer cell lines using membrane permeabilization prior to Mannitou staining have previously indicated that paucimannosidic glycoepitopes are also located intracellularly …”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Similar cancer cell surface expression of PMGs was detected for a related human glioblastoma cell line (U138MG) (data not shown). Immunofluorescence experiments conducted with these and other human cancer cell lines using membrane permeabilization prior to Mannitou staining have previously indicated that paucimannosidic glycoepitopes are also located intracellularly …”
Section: Resultssupporting
confidence: 74%
“…To assess the cancer cell surface expression of paucimannosidic glyco‐epitopes, cultured non‐permeabilized human glioblastoma cells (U87MG and U138MG) were fixed on 0.002% w/v poly‐ l ‐lysine‐coated microscopy glass slides with 4% v/v paraformaldehyde for 20 min. To prevent nonspecific antibody recognition, the fixed cells were treated with a blocking solution containing 5% v/v horse serum in PBS for 20 min, incubated with the PMG‐recognizing mouse IgM “Mannitou” (undiluted supernatant from hybridoma cells for 30 min at room temperature, and then incubated with a goat anti‐mouse IgM Cy2‐conjugated IgG antibody for 30 min in the dark (1:500 dilution, Dianova, Hamburg, Germany) . The immunofluorescence of the cells was determined using a Zeiss Axioplan2 Apotome system equipped with a Plan Apochromat 63×/1.40 oil immersion objective (Zeiss, Oberkochen, Germany) as recently described …”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Recent glycomics and glycoproteomics‐centric studies have demonstrated that PMPs are also elevated glycosylation signatures associated with various human cancers including those of ovarian (Everest‐Dass et al ., ; Chen et al ., ), colorectal (Joosten et al ., ; Balog et al ., ; Sethi et al ., ; Kaprio et al ., ; Holst et al ., ), breast (Lee et al ., ; Chen et al ., ), lung (Hua et al ., ; Ruhaak et al ., ; Wang et al ., ), paraganglioma (Leijon et al ., ), glioblastoma multiforme (Becker et al ., ), skin (Moginger et al ., ) and prostate (Shah et al ., ) origin. By systematically interrogating a very large collection of nearly 500 N ‐glycomics LC‐MS/MS data sets obtained from 11 cancer types and subtypes, we have obtained solid evidence that PMGs are significant features of human cancers and, at least in part, expressed on cancer cell surfaces (S. Chatterjee, L. Y. Lee, R. Kawahara, J. L. Abrahams, B. Adamczyk, M. Anugraham, C. Ashwood, Z. Sumer‐Bayraktar, M. T. Briggs, J. H. L. Chik, A. Everest‐Dass, S. Förster, H. Hinneburg, K. R. M. Leite, I. Loke, U. Möginger, E. S. X. Moh, M. Nakano, S. Recuero, M. K. Sethi, M. Srougi, K. Stavenhagen, V. Venkatakrishnan, K. Wongtrakul‐Kish, S. Diestel, P. Hoffmann, N. G. Karlsson, D. Kolarich, M. P. Molloy, M. H. Muders, M. K. Oehler, N. H. Packer, G. Palmisano & M. Thaysen‐Andersen, in preparation).…”
Section: Human Pmps: Cues From Higher and Lower Eukaryotesmentioning
confidence: 99%
“…Paucimannose represents a relatively simple structure containing N-acetylglucosamines and mannoses (see Figure 1). This epitope per se is involved in immune function [22] and has recently been shown to interfere with brain tumor progression [23]. Since paucimannose was strongly associated with specific molecular weights in Western blot analysis, we tried to identify carrier proteins of the upregulated paucimannose in aged brains.…”
Section: Discussionmentioning
confidence: 99%